2002
DOI: 10.1002/ajp.10038
|View full text |Cite
|
Sign up to set email alerts
|

Hand and body position during locomotor behavior in the aye‐aye (Daubentonia madagascariensis)

Abstract: Aye-ayes (Daubentonia madagascariensis) have unique hands among primates, with extraordinarily long fingers in relation to body size. These long digits may be vulnerable to damage from forces during locomotion, particularly during head-first descent-a locomotor mode that the aye-aye utilizes frequently. Previous behavioral studies of aye-aye locomotion reported that Daubentonia must curl its fingers during horizontal quadrupedalism and/or descent to reduce potential stresses on its long fingers. To test this h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…The common opossum (Didelphis marsupialis) places its manus slightly laterally to the pes on narrow supports (Cartmill, 1974). Finally, the aye-aye (Daubentonia madagascariensis) contacts branches in a wide variety of locations (Krakauer et al, 2002). It is not yet possible to determine whether the kinetic and kinematic patterns observed in the present study represent a general behavioral adaptation to the challenges of arboreal locomotion by terrestrial mammals or simply a solution specific for this species.…”
Section: Behavioral Adaptations For Arboreal Locomotionmentioning
confidence: 99%
“…The common opossum (Didelphis marsupialis) places its manus slightly laterally to the pes on narrow supports (Cartmill, 1974). Finally, the aye-aye (Daubentonia madagascariensis) contacts branches in a wide variety of locations (Krakauer et al, 2002). It is not yet possible to determine whether the kinetic and kinematic patterns observed in the present study represent a general behavioral adaptation to the challenges of arboreal locomotion by terrestrial mammals or simply a solution specific for this species.…”
Section: Behavioral Adaptations For Arboreal Locomotionmentioning
confidence: 99%
“…Aye-ayes, which are able to grasp branches of 80mm in diameter, switch from a 'full-curl' hand position during locomotion on a horizontal branch to a 'full-grip' hand position on slightly ascending branches (30-35deg) (Krakauer et al, 2002). This may be due to the need to generate tensile forces as they move upwards.…”
Section: Kinematic Changes On Inclined Branchesmentioning
confidence: 99%
“…Nakano suggested that this shift in the touch-down position of the forelimbs depends on substrate inclination in each species, which gives rise to the assumption of a significant correlation between limb proportion, inclination and the position of the center of mass (Nakano, 2002). Yet, between 0 and 30deg substrate orientation, forelimbs and hindlimbs in the gray short-tailed opossum are placed in a comparable way (Lammers et al, 2004;Lammers, 2007), and an unmodified body position was also observed in the aye-aye (Krakauer et al, 2002). The influence of limb proportions on locomotor performance is supported by observations regarding differences in limb flexion; elbow and knee joints, for example, are consistently more flexed at touch-down and midstance on sloped branches in primates that possess long limbs (lemurids and lorisids) than in cheirogaleids, which possess short limbs (Stevens, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral studies suggest that aye-ayes curl their fingers off the substrate during horizontal and descending locomotion, placing the entire forelimb load on the palm (Oxnard et al, 1990). However, in a study of arboreal locomotion, Krakauer et al (Krakauer et al, 2002) showed that aye-ayes do not always curl all fingers off the substrate. Instead, they found that the animals in their study used a variety of different hand postures, including postures in which the digits make direct contact with the substrate.…”
Section: Introductionmentioning
confidence: 99%